Unusual Response of Subclavian In-Stent Restenosis to Balloon Angioplasty in a Patient with HIV - Mohammad Atif Rana; Jagan Beedupalli; Nuri I. Akkus (Case Reports in Vascular Medicine)
Human Immunodeficiency Virus (HIV) infection and use of protease inhibitors have been associated with accelerated atherosclerosis. Increased rates of coronary in-stent restenosis are reported in these patients. There is limited data available on peripheral vascular disease interventions on these patients. Herein we report an aggressive subclavian in-stent restenosis with an unexpected response to balloon angioplasty treatment with a large, mobile tissue flap formation and its treatment with another stent.